Allelopathic potential and chemical profile of wheat, rice and barley against the herbicide-resistant weeds Portulaca oleracea L. and Lolium rigidum Gaud. - Eva González-García; Adela M. Sánchez-Moreiras; Yedra Vieites-Álvarez (BMC Plant Biology)
Abstract Background Weeds cause low crop productivity and increasing costs, and therefore, different solutions, such as manual weeding or synthetic herbicides, have been suggested to solve this problem. These methods involve high efforts and costs, in addition to being harmful to the environment in the case of herbicides, which also result in increasing resistance mechanisms in weeds. Therefore, this work addresses the use of in vivo allelopathic crops to control surrounding weeds. To carry out the experiments, co-cultivation of wheat, rice and barley with the monocot weed annual ryegrass (Lolium rigidum Gaud.) and the dicot weed common purslane (Portulaca oleracea L.) was conducted without physical contact among crop and weed plants. Germination and growth parameters of weeds, and growth parameters and chemical profile of crops, were analysed after the end of the experiment. Results The three crops tested caused inhibitory effects on the two target weeds, and significant concentrations of benzoxazinoids were found in the plant tissues and/or root exudates of the different crops in response to the presence of weeds. All the crops showed different responses to the treatments. While the growth of rice was stimulated, barley was not affected, and wheat growth experienced inhibition due to the presence of weeds. Conclusions This study demonstrates the capacity of wheat, rice and barley to inhibit both growth and germination of L. rigidum and P. oleracea. The effects observed could be due to the accumulation and/or exudation of benzoxazinoids such as DIMBOA, DIBOA, BOA or HBOA. Barley and rice are able to sustainably manage both target weeds without disrupting their development, while growth of wheat was affected by the presence of weeds. Based on our results, rice would be the most promising crop, since it has the ability to control weeds, while stimulating the development of rice plants. Nevertheless, more research should be carried out to fully confirm this fact, especially under non-controlled conditions. Graphical Abstract